1958
DOI: 10.1083/jcb.4.5.575
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical Localisations and Ultrastructure in the Fertilized Unsegmented Egg of Paracentrotus lividus

Abstract: Fertilized, but still unsegmented, eggs of the sea urchin Paracentrotus llvidus have been centrifugated at 30,000 gravity. A comparison has been made between the cytochemical reactions of the different layers (RNA, polysaccharides, acid phosphatase) and the fine structure as shown in thin sections studied with the electron microscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1965
1965
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Merriam (21) has pointed out that annulate lamellae in sand dollar oocytes have a high intrinsic density which does not disappear when the section is bleached with hydrogen peroxide, and hence, they react to the treatment in the same way as the 150 A particles of the heavy bodies. Several studies (1,11,28) on various sea urchin oocytes have shown that annulate lamellae may be associated with masses of ribonucleoprotein; the latter probably are derived from the nucleolar material of the nucleus (1). Examples of annulate lamellae that are continuous at their ends with granular endoplasmic reticulum are numerous (4, 6-10, 13, 15, 17, 18, 28, 30-32).…”
Section: Discussionmentioning
confidence: 99%
“…Merriam (21) has pointed out that annulate lamellae in sand dollar oocytes have a high intrinsic density which does not disappear when the section is bleached with hydrogen peroxide, and hence, they react to the treatment in the same way as the 150 A particles of the heavy bodies. Several studies (1,11,28) on various sea urchin oocytes have shown that annulate lamellae may be associated with masses of ribonucleoprotein; the latter probably are derived from the nucleolar material of the nucleus (1). Examples of annulate lamellae that are continuous at their ends with granular endoplasmic reticulum are numerous (4, 6-10, 13, 15, 17, 18, 28, 30-32).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ribosomes associated with the annulate lamellae in tunicate oocytes might warrant the assumption that these lamellae represent a specialized form of the endoplasmic reticulum in addition to the many rough-surfaced vesicles present in the ooplasm. However, the structural differences between the granular endoplasmic reticulum and annulate lamellae may also suggest functional differences between the two systems which, in some cells, are observed to be continuous (Rebhun, 1961). Certainly, differences in the physical nature and viscosity of the materials associated with the annulate lamellae as compared to the vesicular endoplasmic reticulum are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…In some cells, ribosomes appear to be associated with annulate lamellae in the cytoplasm (Afzelius, 1957;Merriam, 1959;Kessel, 1964 b) while, in other instances, riboncleoprotein particles have not been observed to be associated with them (Rebhun, 1956;Ruthmann, 1958). The presence of ribosomes associated with the annulate lamellae in tunicate oocytes might warrant the assumption that these lamellae represent a specialized form of the endoplasmic reticulum in addition to the many rough-surfaced vesicles present in the ooplasm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations